Reaktualisasi Pendidikan Politik dalam Menghadapi Politik Uang Melalui Gerakan Desa Anti Politik Uang - Yuan Febriyanti Alina (Universitas Warmadewa, 2022)
Regional Head Elections in Indonesia still face major problems related to the phenomenon of money politics so that its existence is difficult to stop so that it has been cultivated in the community. This study examines efforts to prevent the practice of money politics through strengthening political education in the form of the Anti-Money Politics Village Movement. Through such efforts, it is hoped that it will be able to become a solution in alleviating the rampant phenomenon of money politics. The purpose of this paper is to find out how the Anti-Money Politics Village has become a means of political education in the face of money politics. This research uses qualitative methods with a descriptive approach. The method was chosen to explain in more depth the phenomenon under study. The research location is in Nglanggeran Village, Patuk District, Gunungkidul Regency. Data collection was carried out through in-depth interview techniques with the actors and the community involved as many as four people. In addition, data in the form of literature studies and documentation become secondary data that also complements and plays a role in checking the data that has been obtained through previous techniques. The results of the study found that, The APU Village Movement as a new breakthrough in preventing the rapid phenomenon of money politics through the provision of cultural political education to the people in Nglanggeran Village. Through this political education, it makes a society's political awareness increase so that it is able to become an agent who firmly rejects, resists, and reports on all practices of money politics. Political education carried out by Bawaslu in order to grow and increase the political awareness of the community itself encourages and motivates the community to become smart and desicive voters, encourages political parties, presidential and regional elections to contest in a clean and healthy manner, as well as to be creative and innovative in campaigning. Of course, this political education is rooted in the spirit of the APU Village Movement, which is to undermine every village in order to participate in monitoring, refusing, resisting and reporting malpractices such as politics in every electoral democracy party.